Primary selection of the prebiotic components in the complex dermatological therapeutic and preventive medicine with probiotic - Soloviova, Alina; Kaliuzhnaia, Olha; Strelnikov, Leonid (ScienceRise: Pharmaceutical Science, 2020)
The aim. Selection of optimal prebiotic components for bacteria of the genus Lactobacillus for their joint use in a complex dermatological therapeutic and preventive medicine with a probiotic. Methods. Co-cultivation of a probiotic strain in a liquid MRS nutrient medium with an active ingredient at selected concentrations. During the cultivation cycle, samples of growing culture were selected at specific intervals to determine bacterial concentration by direct seeding and acidity determination. Results. During 48 h of co-cultivation of lactobacilli with selected components, were observed a significant increase of viable cells, both in control and with the addition of vitamins at selected concentrations (exponential bacterial growth phase), from 48 h to 60 h - decrease of the rate of cell growth as in control group, and in experiments, the number of cells remains almost constant (stationary phase of bacterial growth), after 60 h - decrease of the number of cells (phase of dying). During cultivation, the oxidation of the nutrient medium resulting from the formation of lactic acid carbohydrates and other terminal metabolites were observed; that is, the addition of components slightly increases the biochemical potential of microorganisms, as evidenced by the increase in biomass and acid potential. Although there was no significant difference between one series of experiments with different vitamin contents, the largest increase in viable cell was observed with vitamin B5 (concentration 1 %) and provitamin B5 (concentration 2.5 %). Conclusions. Optimal prebiotic components for use with lactobacilli as part of dosage form were selected. Despite the pronounced synergism of action of the vitamin B5 and D-panthenol, all other components are also promising due to the positive effects on human skin and lack of negative effects on lactobacilli